Covid 19 Tragedy as a Momentum for Nahdlatul Ulama and Muhammadiyah to Support Palestine : A Coxian Perspective - Dwi Ardiyanti; Virtuous Setyaka; Zahidiyah Ela Tursina; Warosuatun Khadijah; Laksitannisa Harumi; Ratna Alfina Nurcahyani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to provide solutions recommendations so that Palestine can get out of the double tragedy. Palestine is said to be experiencing a double tragedy because Palestine is a victim of Israeli colonialism as well as experiencing the Covid 19 pandemic. This research used Robert Cox perspective, are concept of independence economic management through strategy of take advantage of foreign aid and concept of historical bloc which used by Palestinian people for free from Israeli colonialism. The organizations movements analysed in this study are Nahdlatul Ulama (NU) and Muhammadiyah. This research resulted in two solutions recommendations, namely, first, NU and Muhammadiyah should strengthen cooperation in providing assistance to the Palestinian people. This is done in order to create economic independence for the Palestinian people so that they can become a social force capable of fighting Israeli colonialism. Second, NU and Muhammadiyah should strengthen cooperation to support the historical bloc so that Palestine can be free from Israeli colonialism. Actually, both of organizations can become social power which have ability of counter hegemony Israeli power. This research is a correlative/predictive research, namely by explaining Robert Cox's concepts to find out possible solutions that can be taken to solve problems.